2020
DOI: 10.3390/cells9061460
|View full text |Cite
|
Sign up to set email alerts
|

How HP1 Post-Translational Modifications Regulate Heterochromatin Formation and Maintenance

Abstract: Heterochromatin Protein 1 (HP1) is a highly conserved protein that has been used as a classic marker for heterochromatin. HP1 binds to di- and tri-methylated histone H3K9 and regulates heterochromatin formation, functions and structure. Besides the well-established phosphorylation of histone H3 Ser10 that has been shown to modulate HP1 binding to chromatin, several studies have recently highlighted the importance of HP1 post-translational modifications and additional epigenetic features for the modulation of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 102 publications
(133 reference statements)
1
14
0
Order By: Relevance
“…With mutation analyses, we identified that the HP1β-pS89 is catalyzed by CK2 in cells, which is in line with in vitro phosphorylation assay following mass spectrometry analyses ( 60 , 61 ). This phosphorylation generates a specific binding site for KAP1 that provides a link to pluripotency as KAP1 has been identified as an essential factor that represses differentiation-inducible and derepresses pluripotency-associated genes ( 57 , 62–65 ).…”
Section: Discussionsupporting
confidence: 71%
“…With mutation analyses, we identified that the HP1β-pS89 is catalyzed by CK2 in cells, which is in line with in vitro phosphorylation assay following mass spectrometry analyses ( 60 , 61 ). This phosphorylation generates a specific binding site for KAP1 that provides a link to pluripotency as KAP1 has been identified as an essential factor that represses differentiation-inducible and derepresses pluripotency-associated genes ( 57 , 62–65 ).…”
Section: Discussionsupporting
confidence: 71%
“…It was suggested that TFs act in a combinatorial fashion and may exhibit pleiotropic functionality [ 33 , 39 , 40 ]. Alternatively, they might interact with additional regulatory proteins [ 36 , 41 ], or undergo post-transcriptional modification like other epigenetic regulators [ 42 , 43 , 44 ].…”
Section: Dna-based Featuresmentioning
confidence: 99%
“…Also mammalian HP1 isoforms undergo specific modifications including phosphorylation, acetylation, methylation, formylation, ubiquitination, SUMOylation and citrullination (Minc et al 1999;Lomberk et al 2006;LeRoy et al 2009;Maison et al 2011;Wiese et al 2019;Sales-Gil and Vagnarelli 2020). Similarly to Drosophila HP1, each of these modifications can change HP1 functions, thus creating an epigenetic subcode that would permit different interactions of HP1 in different chromatin contexts.…”
Section: Introductionmentioning
confidence: 99%